Community-level social participation and functional disability among older adults: A JAGES multilevel longitudinal study. (May 2022) - Fujihara, Satoko; Miyaguni, Yasuhiro; Tsuji, Taishi; Kondo, Katsunori
Highlights: This is 6-year cohort design utilizing a large sample of older adults in Japan. Community-level sports and hobby group participation prevent functional disability. Neighborhood group participation prevents functional disability among females. Promoting social participation in communities might prevent functional disability . Abstract: Purpose: This study investigates the contextual association between types of community-level social participation and functional disability. Methods: We used 6-year prospective cohort data from the Japan Gerontological Evaluation Study 2010–2016, a nationwide survey of 35, 519 functionally independent older adults (mean age: 73.30 ± 5.91 years, 49.6% females). The incidence of functional disability was obtained from municipal long-term care insurance databases. Social participation was assessed at individual and community levels and was categorized as: volunteer, sports, hobby and neighborhood groups, and senior citizen clubs. We calculated the 95% confidence interval (CI) and the hazard ratio (HR) by applying a three-level multilevel survival analysis. Results: During the 6-year observation period, the onset of functional disability occurred among 3473 adults. A higher prevalence of sports (HR 0.88, 95% CI 0.80 to 0.96) and hobby group participation (HR 0.91, 95% CI 0.87 to 0.96) showed significant contextual relationships with functional disability after adjusting for potential confounders. Among females, community-level neighborhood group participation significantly lowered the incidence of functional disability (HR 0.87, 95% CI 0.76 to 0.998). Conclusions: We found a beneficial effect of a contextual relationship between community-level sports and hobby group participation and functional disability among older adults. Moreover, females benefited a lot from community-level social participation. We propose that promoting sports and hobby groups in a community may help to prevent functional disability among older adults.